Genetic Analysis Reveals That C₁₉-GA 2-Oxidation Is a Major Gibberellin Inactivation Pathway in Arabidopsis - Rieu, Ivo; Eriksson, Sven; Powers, Stephen J; Gong, Fan; Griffiths, Jayne; Woolley, Lindsey; Benlloch, Reyes; Nilsson, Ove; Thomas, Stephen G; Hedden, Peter; Phillips, Andrew L (The Plant cell, 2008)
Bioactive hormone concentrations are regulated both at the level of hormone synthesis and through controlled inactivation. Based on the ubiquitous presence of 2β-hydroxylated gibberellins (GAs), a major inactivating pathway for the plant hormone GA seems to be via GA 2-oxidation. In this study, we used various approaches to determine the role of C₁₉-GA 2-oxidation in regulating GA concentration and GA-responsive plant growth and development. We show that Arabidopsis thaliana has five C₁₉-GA 2-oxidases, transcripts for one or more of which are present in all organs and at all stages of development examined. Expression of four of the five genes is subject to feed-forward regulation. By knocking out all five Arabidopsis C₁₉-GA 2-oxidases, we show that C₁₉-GA 2-oxidation limits bioactive GA content and regulates plant development at various stages during the plant life cycle: C₁₉-GA 2-oxidases prevent seed germination in the absence of light and cold stimuli, delay the vegetative and floral phase transitions, limit the number of flowers produced per inflorescence, and suppress elongation of the pistil prior to fertilization. Under GA-limited conditions, further roles are revealed, such as limiting elongation of the main stem and side shoots. We conclude that C₁₉-GA 2-oxidation is a major GA inactivation pathway regulating development in ARABIDOPSIS: